2017
DOI: 10.1002/pssa.201600691
|View full text |Cite
|
Sign up to set email alerts
|

Spin–orbit coupling and Lorentz force enhanced efficiency of TiO2‐based dye sensitized solar cells

Abstract: We report on the effect of the strong spin -orbit coupling and the Lorentz force on the efficiency of TiO 2 based dye sensitized solar cells. Upon inclusion of Ho 2 O 3 , due to the strong spin -orbit coupling of the rare earth Ho 3+ ion, we do see 13% enhancement in the efficiency. We attribute such an enhancement in power conversion efficiency to the increased lifetime of the photoexcited excitons. Essentially, a Ho 3+ ion accelerates the phenomenon of the spin -rephasing or the intersystem crossing of the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The transitions between pure spin states of different multiplicities are, as it is well known, forbidden by the spin selection rules. However, several spin-forbidden intersystem crossings in organic and inorganic systems are reported to be essential for a specific action in different areas [ 1 , 2 , 3 ]. It is known that these transitions can occur as result of a spin–orbit coupling (SOC), a relativistic effect that induces a quantum mechanical mixing between states with different spin multiplicity.…”
Section: Introductionmentioning
confidence: 99%
“…The transitions between pure spin states of different multiplicities are, as it is well known, forbidden by the spin selection rules. However, several spin-forbidden intersystem crossings in organic and inorganic systems are reported to be essential for a specific action in different areas [ 1 , 2 , 3 ]. It is known that these transitions can occur as result of a spin–orbit coupling (SOC), a relativistic effect that induces a quantum mechanical mixing between states with different spin multiplicity.…”
Section: Introductionmentioning
confidence: 99%
“…The ecological problems arising from the excessive use of inorganic switching materials and newer requirements for biodegradable devices have pushed the research towards developing alternate organic-based devices for several conventional devices like transistors [ 109 ], batteries [ 110 ], solar cells [ 111 ], LEDs [ 112 ], etc. A number of RRAM devices have also been reported based on unique organic-material-based device designs [ 113 ].…”
Section: Resistive Switching Materials and Applicationsmentioning
confidence: 99%
“…Recently in 2018, Kannan et al presented that in Ho 3+ ‐doped TiO 2 (HTO), the number of dissociated charges carriers increases because of intersystem crossing due to which current density was increased in HTO as compared to bare TiO 2 device. The strong spin‐orbit coupling of RE Ho 3+ ion increases the rate of excitonic dissociation from excited singlet electronic state to triplet excitonic state, which leads to enhancement in the charge dissociation process. Authors found that in the presence of a magnetic field, power conversion efficiency of HTO devices increased by 36.5% as compared to TO devices.…”
Section: Re‐doped Tio2 For Spectral Conversionmentioning
confidence: 99%